A novel approach for bone scaffold from oil palm empty fruit bunch cellulose phosphate / glass material - M. Yusup, Eliza; Mahzan, Shahruddin; Mohammad, Baharuddin; Wan Daud, Wan Rosli (Trans Tech Publications, 2013)
Current trend has demonstrated the implementation of natural polymers as alternative materials in various engineering applications including biomaterials and biomedical applications. This paper reviews the potential of Cellulose Phosphate derived from Oil Palm Empty Fruit Bunch (OPEFB-CP) as a biomedical material. OPEFB-CP will act as reinforcement to glass materials in fabricating good and flexible scaffold composite materials. A 3-dimensional scaffold composite material comprised of the cellulose phosphate and glass material was produced by using a sol-gel technique. The composite biomaterial is expected to have degraded together as one material.